How do independent directors view CEO pay disparity in China? - Muhammad Abubakkar Siddique; Shagufta Jafar; Muhammad Usman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
Given the vital role of independent directors in determination of executives' compensation, we explore how independent directors view the CEO pay disparity. Using the data of all companies listed on the Shenzhen and Shanghai stock exchanges for the period 2005 to 2015, we find that the proportion of independent directors on the board is negatively associated with the extent to which executives' pay is dispersed. This finding suggests that independent directors view the dispersion of the CEO's and other executive directors' pay from the managerial power theory perspective rather than from the tournament theory.
Keywords: 330; CEO pay disparity; CEO tenure; China; independent directors; managerial power; and state owned firms; tournament incentives